2018
DOI: 10.1111/imig.12508
|View full text |Cite
|
Sign up to set email alerts
|

Syrian Refugees Living on the Edge: Policy and Practice Implications for Mental Health and Psychosocial Wellbeing

Abstract: This qualitative study aims to explore the difficulties experienced by Syrian refugees living in the camps of Turkey in the pre‐migration and post‐migration environment and the impacts thereof on their mental wellbeing. Semi‐structured interviews were conducted with Syrian refugees living in three different camps on the Syrian border of Turkey. Syrian refugees were highly exposed to traumatic events in the pre‐migration period, including armed conflicts, human rights violations, and social and economic devasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Actually, health inequality can result in discrimination against refugees, and discrimination is a well-known social determinant of health, and have the potential to exacerbate negative health and well-being outcomes (Priebe et al, 2011). There are some Turkish researches regarding the health needs of refugees (Cantekin, 2019;Sahlool et al, 2012;Assi et al, 2019). In many studies, refugees have not been identified as a homogeneous group and stated that they have different experiences and expectations of health and of health care and as a result, they have various healthcare needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, health inequality can result in discrimination against refugees, and discrimination is a well-known social determinant of health, and have the potential to exacerbate negative health and well-being outcomes (Priebe et al, 2011). There are some Turkish researches regarding the health needs of refugees (Cantekin, 2019;Sahlool et al, 2012;Assi et al, 2019). In many studies, refugees have not been identified as a homogeneous group and stated that they have different experiences and expectations of health and of health care and as a result, they have various healthcare needs.…”
Section: Discussionmentioning
confidence: 99%
“…Following the anti-regime demonstrations that started in March 2011, the developments in Syria created one of the biggest humanitarian crises in the world. On a population basis, Syria still has the highest number of refugees or asylum seekers population worldwide, with 12.6 million people (almost two-thirds of its population) (Cantekin, 2019). Turkey serves millions of refugees to the host due to its strategic location (Turkey shares the longest land border with Syria).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the ability of the state to offer health care insurance and provide health care services for the Syrian refugee population, the relative weakness of Turkish mental health services, the inability to offer services in the mother tongue of the refugee population and the centrality of the use of mother tongue in mental health services leave the mental health needs of the refugees – which increased with post-migration experiences (Cantekin, 2018: 8–12) – largely unmet. The Ministry of Family and Social Policies offers psychosocial support services mainly in temporary accommodation centres (Hürriyet, 2017).…”
Section: The Humanitarian Response and The Development Of Social Polimentioning
confidence: 99%
“…The increase has heaved in sight in demographic mobility, increasing from 33.9 million in 1997 to 68.5 million in 2017 (UNHCR, 2017). One of the major reasons for the increase is the Syrian civil war (Cantekin, 2019). One of the greatest demographic movements of the century was experienced with the start of the war in 2011.…”
Section: Introductionmentioning
confidence: 99%